«SOFT SKILLS» IN THE FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE SOCIAL WORKERS - Stynska, Viktoriia; Protas, Oksana (Mountain School of Ukrainian Carpaty, 2023)
The article is devoted to the trajectory of «soft skills» development in the formation of professional competence of future social workers. Based on the analysis of scientific literature, the essence of the concept of «soft skills» is highlighted, by which we mean a set of professionally and socially important skills that students acquire during vocationally oriented education in higher education institutions, which ensures their competitiveness in future professional activities. It is established that in the triad of skills of the future social worker: hard skills, soft skills and digital skills - soft skills are the basis for the effective mastery of hard skills, and digital skills are the guiding vector of modern professional competencies. The most important soft skills for the formation of professional competence in future social workers are summarized, namely: - communication skills (public speaking, presentation, personal brand, self-presentation, negotiation, conflict management, storytelling, interpersonal communication, business ethics, professional ethics, intercultural competence, networking); - management skills (leadership, team building, motivation, project management, organization/organization, trustworthiness, result orientation, planning, time management/resource management, civic engagement, mentoring/ facilitation, supervision); - personal effectiveness skills (emotional intelligence, empathy, solving difficult situations, lifelong development, stress resistance, quick response, effectiveness under risk, client focus, creativity, reframing, initiative, innovation); - information processing skills (flexibility of thinking, critical thinking, data search/analysis/synthesis, media literacy, observation, prudence, analytical thinking, logical reasoning, monitoring, trends in the professional field, processing of large amounts of information, establishing relationships); - strategic skills (tactical thinking, strategic thinking, decision-making, resourcefulness, image, alternatives, priority, systemic thinking, structural thinking, research thinking, problem-oriented thinking). It is concluded that one of the most important aspects of the formation of professional competence of future social workers is «soft skills», which allows them to prepare for work in innovative conditions of fierce competition in the market of educational services.